Effect of bioaugmentation using Clostridium butyricum on the start-up and the performance of continuous biohydrogen production. (December 2022) - Sim, Young-Bo; Yang, Jisu; Kim, Saint Moon; Joo, Hwan-Hong; Jung, Ju-Hyeong; Kim, Do-Hyung; Kim, Sang-Hyoun
Graphical abstract: Highlights: Heat-treated sludge with Clostridium butyricum produced H2 at 58.57 ± 5.03 L/L-d. Sludge-originated H2 -producers rather than C. butyricum dominated the grown culture. C. butyricum prevented the growth of Streptococcus, Lactobacillus and Megasphaera. Initial abundance of Clostridium over 71.3% is recommended for a continuous culture. Abstract: This study aimed to mitigate the instability in the start-up and continuous performance of dark fermentative biohydrogen production using heat-treated sludge by the addition of an exogenous H2 -producing strain. Continuous fermentation augmented with Clostridium butyricum showed the highest average biohydrogen production rate (HPR) as 50.35 ± 2.56 and 58.57 ± 5.03 L/L-d with H2 -producing butyric and acetic acid pathways, whereas the fermenters without bioaugmentation showed the termination of biohydrogen production in 3 days of continuous operation with non H2 -producing lactic acid pathway and H2 -consuming propionic acid pathway. The bioaugmentation blocked the growth of the competitors for hexose such as Streptococcus, Lactobacillus and Megasphaera, and provided H2 -producer dominated microbiome with not only Clostridium butyricum, but also Clostridium puniceum and Clostridium neuense originated from heat-treated sludge. Bioaugmentation of a H2 -producing strain would be a reliable dissemination strategy for dark fermentative biohydrogen production by minimizing the influence of seed sludge population.